2019
DOI: 10.1016/j.dr.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Interventions targeting working memory in 4–11 year olds within their everyday contexts: A systematic review

Abstract: Highlights Non-computerised training can improve working memory and near-transfer skills. Training other skills (physical activity, play, inhibition) is beneficial indirectly. Tapping into attentional resources (executive control) is key to task effectiveness. Further studies need clear theoretical underpinnings and rigorous methodology. Outcome measurement and dosage need greater consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 113 publications
1
16
0
3
Order By: Relevance
“…This novel intervention targets WM explicitly and is based on a systematic review of evidence suggesting that repeated practice on certain (non-computerised) activities can improve WM and have the potential to produce effects on untrained WM skills (near-transfer) and real-world skills such as attention and language (far-transfer) [ 39 ]. The common ingredient across the effective interventions was the executive-loaded nature of the trained task, i.e., training on a task that taps into attentional and processing resources under executive control and not just the storage of information.…”
Section: Methodsmentioning
confidence: 99%
“…This novel intervention targets WM explicitly and is based on a systematic review of evidence suggesting that repeated practice on certain (non-computerised) activities can improve WM and have the potential to produce effects on untrained WM skills (near-transfer) and real-world skills such as attention and language (far-transfer) [ 39 ]. The common ingredient across the effective interventions was the executive-loaded nature of the trained task, i.e., training on a task that taps into attentional and processing resources under executive control and not just the storage of information.…”
Section: Methodsmentioning
confidence: 99%
“…The tasks included in RECALL are based on evidence from a recent systematic review [56]. The review found certain tasks designed to either target WM directly (listening recall and odd-one-out) or indirectly (cognitively-demanding physical activity, inhibition, phoneme awareness and fantastical play) produced improvements on WM and some benefits for near-transfer activities [5767].…”
Section: Methodsmentioning
confidence: 99%
“…The common ingredient across the effective interventions was predominantly the executive-loaded nature of the trained task, i.e. training on a task that taps into attentional and processing resources under executive control and not just the storage of information [56]. It has been suggested that repeated practice on executive-loaded working memory (ELWM) tasks (rather than practising storage-only, short-term memory tasks) may improve the efficiency of processing or perhaps even facilitate the storage of information in WM [58, 68].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the information is no longer available, they must choose from the latter options. Both are likely to lead to missed learning opportunities, which when occurring frequently, can significantly restrict learning (Holmes et al, 2010;Rowe et al, 2019).…”
mentioning
confidence: 99%